Simultaneous onset of type 1 diabetes mellitus and silent thyroiditis under durvalumab treatment. (15th July 2019) - León Mengíbar, Jose; Capel, Ismael; Bonfill, Teresa; Mazarico, Isabel; Casamitjana Espuña, Laia; Caixàs, Assumpta; Rigla, Mercedes
Summary: Durvalumab, a human immunoglobulin G1 kappa monoclonal antibody that blocks the interaction of programmed cell death ligand 1 (PD-L1) with the PD-1 and CD80 (B7.1) molecules, is increasingly used in advanced neoplasias. Durvalumab use is associated with increased immune-related adverse events. We report a case of a 55-year-old man who presented to our emergency room with hyperglycaemia after receiving durvalumab for urothelial high-grade non-muscle-invasive bladder cancer. On presentation, he had polyuria, polyphagia, nausea and vomiting, and laboratory test revealed diabetic ketoacidosis (DKA). Other than durvalumab, no precipitating factors were identified. Pre-durvalumab blood glucose was normal. The patient responded to treatment with intravenous fluids, insulin and electrolyte replacement. Simultaneously, he presented a thyroid hormone pattern that evolved in 10 weeks from subclinical hyperthyroidism (initially attributed to iodinated contrast used in a previous computerised tomography) to overt hyperthyroidism and then to severe primary hypothyroidism (TSH: 34.40 µU/mL, free thyroxine (FT4): <0.23 ng/dL and free tri-iodothyronine (FT3): 0.57 pg/mL). Replacement therapy with levothyroxine was initiated. Finally, he was tested positive for anti-glutamic acid decarboxylase (GAD65), anti-thyroglobulin (Tg) and antithyroid peroxidase (TPO) antibodies (Abs) and diagnosed with type 1 diabetes mellitus (DM) and silent thyroiditis caused by durvalumab. When durvalumab was stopped, he maintained the treatment of multiple daily insulin doses and levothyroxine. Clinicians need to be alerted about the development of endocrinopathies, such as DM, DKA and primary hypothyroidism in the patients receiving durvalumab. Learning points: Patients treated with anti-PD-L1 should be screened for the most common immune-related adverse events (irAEs). Glucose levels and thyroid function should be monitored before and during the treatment. Durvalumab is mainly associated with thyroid and endocrine pancreas dysfunction. In the patients with significant autoimmune background, risk–benefit balance of antineoplastic immunotherapy should be accurately assessed.